Understanding The Molecular Enteropathogenesis Of Martx Toxin Genes And Cholera Toxin Gene Mutations Of Vibrio Cholerae O139 Serogroup Towards Cholera Vaccine Development - Tan , Gim Cheong (2010)

(untitled)
Cholera is a lethal diarrheal disease caused by toxigenic V. cholerae of O1 and O139 serogroups. Early diagnosis and prompt treatments of the disease are needed to prevent death in these patients. Even though the spreading of the disease could be controlled with proper sanitation, the best way to prevent cholera is through vaccination. There are several cholera vaccines available for O1 serogroup V. cholerae but they do not cross-protect against O139 serogroup. The bivalent O1/O139 cholera vaccine also did not show satisfactory protective immune response against O139 serogroup in clinical trials. Hence, the objective of this study is to construct an attenuated live cholera vaccine against V. cholerae O139 serogroup. In the present study, we focused on mutational analysis of MARTX toxin and cholera toxin of V. cholerae O139 serogroup. Constructed rtxC (VCUSM9P) and rtxA/C (VCUSM10P) mutants of V. cholerae O139 serogroup showed depleted in cytotoxic properties.